2017
DOI: 10.1590/1982-0224-20160142
|View full text |Cite
|
Sign up to set email alerts
|

Is coexistence between non-native and native Erythrinidae species mediated by niche differentiation or environmental filtering? A case study in the upper Paraná River floodplain

Abstract: The limiting similarity theory predicts that divergence in the functional traits of native and introduced species is an essential component in species establishment, as introduced species must occupy a niche that is unoccupied by resident species. On the other hand, the environmental filtering hypothesis predicts convergence between introduced and native species, as both possess traits that make them adapted to the local abiotic environment. Morphology, spatial co-occurrence, diet, feeding selectivity, and nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Our results also showed that the native Hoplias has a wider niche area, whereas the non-native obtains resources at higher trophic levels. A similar outcome was observed by Alves, Figueiredo, et al (2017) For Hoplias, we expected trophic segregation to be an outcome of distinct foraging behaviours derived from differential ecomorphological features, as hypothesised by Strictar-Pereira et al (2017) for the same floodplain. The native Hoplias sp.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Our results also showed that the native Hoplias has a wider niche area, whereas the non-native obtains resources at higher trophic levels. A similar outcome was observed by Alves, Figueiredo, et al (2017) For Hoplias, we expected trophic segregation to be an outcome of distinct foraging behaviours derived from differential ecomorphological features, as hypothesised by Strictar-Pereira et al (2017) for the same floodplain. The native Hoplias sp.…”
Section: Discussionsupporting
confidence: 79%
“…B presented higher width and height of the head with eyes dorsoventrally positioned, indicating that it occupies benthic positions and is able to ingest larger prey than its non-native congeneric H. mbigua (Strictar-Pereira et al, 2017). Diet composition analysis showed that the native Hoplias consumes preys in lower trophic levels (bottom feeders), whereas the non-native Hoplias diet is mostly derived (over 55%) from piscivorous fish (Strictar-Pereira et al, 2017). Indeed, the isotopic trophic position from this study showed that the non-native species is feeding at a higher trophic level (TP = 3.1) compared to the native species and presents a low proba- McHugh, Budy, Thiede, & VanDyke, 2008;Pilger, Gido, & Propst, 2010;Vander-Zanden, Casselman, & Rasmussen, 1999) and may even decrease the length of food chains (Maceda-Veiga, Nally, & Sostoa, 2018).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations